Emergency Nursing - Rai, Lalita (Journal of Nursing Education of Nepal, 2023)
Emergency nursing is a special field or branch of nursing practice where nurses manage patients in their acute phase of illness or injury. Emergency nurses are trained to adapt to discerning life-threatening problems, prioritize the urgency of care, rapidly and effectively carry out resuscitative measures and provide other treatments. The emergency nurses often have to work under critical and stressful situations. It requires specialized knowledge and training for nurses and effective department management so that quality of care in emergency department is maintained. The objective of this article is to analyze the concept of emergency nursing and the common issues in providing emergency nursing care
Keywords: Emergency; nursing